2018
DOI: 10.1111/ejh.13062
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin regulation in a mouse model of acute hypoxia

Abstract: Spleen and liver are not involved in the early stages of hypoxia-induced hepcidin downregulation. Our data support the role of PDGF-BB and probably also of erythroferrone in the recruitment of iron for erythropoiesis in the hypoxia setting. The rapid normalization of all the erythroid factors against persistent hepcidin suppression suggests that other signals are involved that should be clarified in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Hypoxic stress has been shown to strongly inhibit liver hepcidin production within 15 This is a post-peer-review, pre-copyedit version of an article published in European Journal of Applied Physiology. The final authenticated version is available online at: http://dx.doi.org/10.1007/s00421-019-04157-y h of exposure (Ravasi et al 2018), thereby promoting iron release from (predominantly) reticuloendothelial macrophages in the bone marrow to support erythropoiesis. Hepcidin suppression in hypoxia is not directly mediated by EPO (Canali et al 2016); instead, the hormone erythroferrone (ERFE) is released by proerythroblasts and acts to suppress hepcidin expression (Kautz et al 2014).…”
Section: How Is Iron Metabolism Regulated In Hypoxia?mentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxic stress has been shown to strongly inhibit liver hepcidin production within 15 This is a post-peer-review, pre-copyedit version of an article published in European Journal of Applied Physiology. The final authenticated version is available online at: http://dx.doi.org/10.1007/s00421-019-04157-y h of exposure (Ravasi et al 2018), thereby promoting iron release from (predominantly) reticuloendothelial macrophages in the bone marrow to support erythropoiesis. Hepcidin suppression in hypoxia is not directly mediated by EPO (Canali et al 2016); instead, the hormone erythroferrone (ERFE) is released by proerythroblasts and acts to suppress hepcidin expression (Kautz et al 2014).…”
Section: How Is Iron Metabolism Regulated In Hypoxia?mentioning
confidence: 99%
“…Hepcidin suppression in hypoxia is not directly mediated by EPO (Canali et al 2016); instead, the hormone erythroferrone (ERFE) is released by proerythroblasts and acts to suppress hepcidin expression (Kautz et al 2014). Simultaneously, during early hypoxic exposure, several growth factors in the bone marrow (but not the spleen or liver) may also play a role in hypoxic hepcidin suppression (Ravasi et al 2018). However, since these growth factors and ERFE are downregulated within 48 h, alternative mechanisms have been suggested to regulate the later phases of hepcidin suppression in hypoxia (Ravasi et al 2018).…”
Section: How Is Iron Metabolism Regulated In Hypoxia?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies have found that hypoxia-lowering hepcidin appeared to be related to platelet derived growth factor (PDGF-B) in bone marrow ( 27 , 67 ). When PDGF-B or its receptor was inactivated, inhibition of hepcidin was relieved ( 67 , 68 ), and PDGF-B is a target gene of HIF-1α ( 69 ). Or HIF may be an expression of hepcidin controlled by an indirect way ( 70 ).…”
Section: Roxadustat: a New Option For Treating Inflammatory Anemia Inmentioning
confidence: 99%
“…This short peptide is believed to be responsible for inhibiting the iron release and absorption from macrophages and intestinal epithelial cells, respectively, by binding the only known cellular iron exporter ferroportin [16]. Upregulated HIF-driven erythropoiesis provokes repression of the hepatic hepcidin-encoding gene, although the identity of the soluble mediator of this effect is yet to be confirmed [17][18][19][20]. The drop of serum hepcidin upon hypoxia, eventually, results in elevated iron release from the intestinal epithelium supplying the increased iron demand of expanded erythropoiesis [21].…”
Section: Supracellular Signalingmentioning
confidence: 99%